A comparative study of HIV-1 and HTLV-I protease structure and dynamics reveals a conserved residue interaction network - Ruecker, Pia; Horn, Anselm; Meiselbach, Heike; Sticht, Heinrich (Journal of Molecular Modeling, 2011)
The two retroviruses human T-lymphotropic virus type I (HTLV-I) and human immunodeficiency virus type 1 (HIV-1) are the causative agents of severe and fatal diseases including adult T-cell leukemia and the acquired immune deficiency syndrome (AIDS). Both viruses code for a protease that is essential for replication and therefore represents a key target for drugs interfering with viral infection. The retroviral proteases from HIV-1 and HTLV-I share 31% sequence identity and high structural similarities. Yet, their substrate specificities and inhibition profiles differ substantially. In this study, we performed all-atom molecular dynamics (MD) simulations for both enzymes in their ligand-free states and in complex with model substrates in order to compare their dynamic behaviors and enhance our understanding of the correlation between sequence, structure, and dynamics in this protein family. We found extensive similarities in both local and overall protein dynamics, as well as in the energetics of their interactions with model substrates. Interestingly, those residues that are important for strong ligand binding are frequently not conserved in sequence, thereby offering an explanation for the differences in binding specificity. Moreover, we identified an interaction network of contacts between conserved residues that interconnects secondary structure elements and serves as a scaffold for the protein fold. This interaction network is conformationally stable over time and may provide an explanation for the highly similar dynamic behavior of the two retroviral proteases, even in the light of their rather low overall sequence identity.
EVALuna2:26265